Transthoracic ultrasound versus intraoperative ultrasound in patients with pulmonary fibrosis: Reappraisal of artifacts - Marco Sperandeo; Giulia Gaudiuso; Carla Maria Irene Quarato; Anna Del Colle; Michele Inglese; Francesca Molinaro; Salvatore De Cosmo; Lucia Dimitri; Marco Bizzarri; Elisabettamaria Frongillo (Verduci Editore, 2019)
In the last years, transthoracic ultrasound (TUS) has regained a growing interest from both clinicians and radiologists as a useful and non-invasive diagnostic tool for the study of many pleuropulmonary conditions, including interstitial lung diseases. Intraoperative lung ultrasound (ILU) is an ultrasound technique, developed for lung surface assessment during video-assisted thoracoscopic surgery procedures. It has been developed considering ultrasound basic physical principles for images generation and interpretation. Most of the TUS findings are due to the high difference in acoustic impedance between the chest-wall structures and the air in the lungs. In this brief communication, we compared ILU and TUS images in interstitial lung diseases. Most of the TUS artifacts-based diagnostic algorithms should be reappraised.